الأغراض البلاغية للتقديم والتأخير في القرآن الكريم -عند الألوسي من خلال كتابه روح المعاني- - بن علي, عبد الرؤوف; الساكر, علي (University of Eloued جامعة الجزائر, 2020)
" فهذه مذكرة تحت عنوان: ""الأغراض البلاغية للتقديم والتأخير عند الامام الألوسي من خلال كتابه روح المعاني""، قد جمعنا فيها مجموعة من المواطن التي ذكر فيها الامام ظاهرة التقديم والتأخير، كما خصصنا في هذا البحث مبحثاً تحدثنا فيه عن الإمام وحياته الشخصية والعلمية، وأعطينا نبذة عن كتابه ""روح المعاني""، وسبب تسميته، وأهم مصادره التي اِعتمد عليها الامام، وعالجنا فيها هذا الأسلوب حسب ما أورده الامام في تفسيره. هذا وتعتبر ظاهرة التقديم والتأخير من الظواهر الأساسية في علم البلاغة العربية، ومبحثاً من أهم المباحث التي يقوم عليها علم المعاني، وذلك لاِرتباطها بقصد المتكلم، وأحوال المخاطب ومراعاة مقتضى الحال، ورتبة الكلمة المحفوظة وغير المحفوظة، وذلك من أجل الكشف عن الأسرار واللطائف البلاغية التي تكمن حولها. ومن المعلوم أن لكل نظم ترتيبه وقواعده، ومواقع ألفاظه، ووضع كل كلمة في موقعها المناسب من الجملة، من أهم مقومات البلاغة والبيان، وكثير من الألفاظ لو حدث عليها تقديم وتأخير في مواضعها لأخلت في إبلاغ المعنى، وإيصال الرسالة، أو لضاع جمالها ورونقها وهذا التقديم والتأخير لا يكون عبثاً، إنما يتم وفق ضوابط وقوانين وأسس وضعها علماء البلاغة وجب اِتباعها. وقد تميز القرآن الكريم في نظمه بالدقة في اِختيار الكلمات، وتنسيق مواضعها، حتى قيل فيه أن كل كلمة تعشق موضعها، فلو فرضاً حاولت أن تغيرها –عياذاً بالله-لظهر الخلل والتقديم فيه والتأخير كان لحكمة لغوية، أو نكتة بلاغية، تليق بالسياق العام للآية. وقد أبدع الامام في طرحه لهذه الظاهرة في ثنايا كتابه، وبدورنا قمنا باِستقراء بعضٍ من هذه المواضع من خلال تفسيره، من سورة آل عمران إلى غاية آخر القرآن، طرحنا فيها أقوال الاِمام ودعمناها ببعض أقوال المفسرين، إما للشرح، أو للتعليل والتفصيل. وخلصنا في نهاية الدراسة إلى مجموعة من النتائج، وتركنا فيها بعض التوصيات لطلبة العلم، والباحثين في هذا الموضوع. "This is memoir entitled :’’The Rhetorical purposes for the advancing and delaying according to Imam Alusi , through his book ‘’ Spirit of Meanings ‘’ ‘’ We collected in it a set of positions that he mentioned to a phenomen of the advancement and the delaying , we also devoted in this research a topic in which we talked about the Imam and his personal and scientific life , we were given a brief account of his book “The Spirit of Meanings”, the reason for its name, the most important sources he adopted and we dealt with this method according to what he stated in his explanation . The phenomenon of advancing and delaying is considered one of the basic phenomena in Arabic rhetoric and an article of the most important detective on which the science of meanings is based ; this is due to its association with the intention of the speaker and the case of the listener and taking into account what the situation requires and the rank of the reserved and not reserved word , in order to reveal the secrets and rhetorical witticisms contained in them . It is well known that all systems have their arrangement ,rules and word locations and put each word in its appropriate location ; among the most important elements of rhetoric and statement , many of the words if it happened to them to advance or delay in their places, the meaning would be disturbed or the message may be not conveyed correctly , or lost its beauty and luster, this advancing and delaying are not absurd , Rather, it is carried out according to the rules, laws, and principles established by rhetoric scholars who they must be followed . The Holy Qur’an has distinguished itself in its systems for its accurate selection of words and coordinating their positions until it was said that every word loves its position. If we assume that you tried to change it, God forbid , the defect appears because the advancing and delaying were for a linguistic purpose or rhetorical joke befitting the general context of the verse. The Imam was creative in his presentation of this phenomenon in the folds of his book , on our part, we have extrapolated some of these positions through its interpretation, from Surat Al-Imran to the end of the Qur’an, we put forward the imams ’statements and supported them with some of other explanators’ statements, either for explanation or for detail . We concluded at the end of the study a set of results and we left some recommendations for students and researchers on this topic. And upon Allah is the direction of the (right) way.
مذكرة ماستر تخصص لغة ودراسات قرآنية
Keywords: الأَغْرَاضُ البَلَاغِيَّةُ - التَّقْدِيمِ وَالتَّأْخِير - الْقُرْآنِ الْكَرِيم - الأَلُــــوسِي- رُوحِ المَعَانِـــي; Rhetorical purposes - introduction and delay - the Noble Qur’an - Alalusi - the spirit of meanings